1996
DOI: 10.1001/archsurg.1996.01430210073013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection for Melanoma Metastatic to the Gastrointestinal Tract

Abstract: Almost all patients with melanoma and GI tract metastases can have palliation of symptoms by surgical intervention with minimal morbidity and mortality. The high 5-year survival rate associated with complete surgical resection of GI tract metastases indicates that surgery should be strongly considered for this subgroup of patients with melanoma and distant metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
2
17

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 12 publications
9
200
2
17
Order By: Relevance
“…Os dois fatores mais importantes no prognóstico de sobrevida são a completa ressecção das metástases do trato digestivo e o fato do aparelho digestivo ser o sítio primário destas metástases 7 . A sobrevida média em cinco anos varia de 18 a 28.3% dos casos 1 .…”
Section: Discussionunclassified
“…Os dois fatores mais importantes no prognóstico de sobrevida são a completa ressecção das metástases do trato digestivo e o fato do aparelho digestivo ser o sítio primário destas metástases 7 . A sobrevida média em cinco anos varia de 18 a 28.3% dos casos 1 .…”
Section: Discussionunclassified
“…Contrary to what might be expected, though, several studies have shown a survival benefit in patients with metastatic melanoma to the gastrointestinal tract that undergo curative resection. In a review of 124 patients who underwent surgical resection of metastatic melanoma between 1971-1994, resection with curative intent had a median survival of 49 months whereas resection for palliation was only 5.4 months [12]. Multivariate analysis identified curative intent and gastrointestinal tract as the initial metastatic site as predictive of long-term survival.…”
Section: Case Reportmentioning
confidence: 99%
“…When complete resection is performed in the setting of distant disease, five-year survival rates in the range of 20-25%, and as high as 40%, may be achieved . Importantly, one study showed that, while patients who undergo complete resection of metastatic melanoma have a 5 year survival rate of 23%, the figure was 6% in patients who either do not undergo surgery or have gross residual disease remaining following surgery (R2 resection) [Agrawal et al, 1999;Essner et al, 2004;Ollila et al, 1996;Rose et al, 2001].…”
Section: Resection Of Distant Metastatic Diseasementioning
confidence: 99%